Florence Deakins Becker papers - Becker, Florence Deakins, 1878-1969.
Correspondence, diaries, speeches, writings, subject files, family papers, scrapbooks, and other papers relating principally to Becker's volunteer activities on behalf of various health and medical causes, especially the crusade against cancer and tuberculosis. Documents her work with the George Ferdinand Becker Memorial Library, Independence, Va.; Ligue du Nord Contre la Tuberculose; Tuberculosis Association of Bengal; and Urgent Relief for France. Subjects include American efforts to render medical aid to French refugees during World War I, the Maryland tercentenary, medical conditions in veterans's hospitals, the Michigan Tuberculosis Association, and the Washington Animal Rescue League. Correspondents include American Public Health Association, Clarence W. Barron, Suzanne Earle Ogden-Jones Emmons Bartlett, George F. Becker, Joseph Colt Bloodgood, William Edgar Borah, W. Norman Brown, Edward T. Devine, William P. Dillingham, John Campbell Forrester, Florence Keen, Thomas E. Rush, and William H. Taft.
Library of Congress Prints and Photographs Division.
Nurse and volunteer worker.
Collection material in English and French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barron, Clarence W. -- 1855-1928 -- Correspondence; Bartlett, Suzanne Earle Ogden-Jones Emmons, -- 1861-1954 -- Correspondence; Becker, George F. -- 1847-1919 -- Correspondence; Bloodgood, Joseph Colt, -- 1867-1935 -- Correspondence; Borah, William Edgar, -- 1865-1940 -- Correspondence; Brown, W. Norman -- 1892-1975 -- Correspondence; Devine, Edward T. -- 1867-1948 -- Correspondence; Dillingham, William P. -- 1843-1923 -- Correspondence; Forrester, John Campbell -- Correspondence; Keen, Florence -- Correspondence; Rush, Thomas E., -- 1867-1947 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; American Public Health Association -- Correspondence; George Ferdinand Becker Memorial Library; Ligue du Nord Contre la Tuberculose; Michigan Tuberculosis Association; Tuberculosis Association of Bengal; Urgent Relief for France; Washington Animal Rescue League; Animal rescue -- Washington (D.C.) -- Societies, etc; Cancer -- Prevention; Health; Libraries -- Virginia -- Independence; Veterans' hospitals; Nursing; Public health -- Societies, etc; Refugees -- France; Tuberculosis -- Prevention; Tuberculosis -- France -- Prevention; Tuberculosis -- India -- Prevention; Tuberculosis -- United States -- Prevention; World War, 1914-1918 -- Medical care; Maryland -- Centennial celebrations, etc; Nurses; Volunteers